"The Names of Streets and Neighborhoods in Abha "Semiotics Study - Al Husami, Abdul Hamid Saif; Abu Taleb, Ibrahim Mohammed; Haidar, Hassan Ahmed; Al-Adbaay, Abdul Ghani Shawqi; Al-Afiri, Abdul Qawi Ali; Al-Jawzi, Abdullah Ali; Sweileh, Fawzi Ali (Arab Journal for Sciences and Research Publishing, 2019)
This research aims to study the names of streets and neighborhoods in Abha in a semiotics studying approach, studying the famous elements and their diversity, and their various evidences through their religious, cultural, and political backgrounds. Studying the place with its many regions of mountains, valleys, villages, cities, and various landmarks internally and externally, and then follows the names of time with indicators of days and weeks, and finally emphasizes on the impact of the different races of plants, Birds and other natural species.